Research on the assessment of historic city conservation planning implementation based on fuzzy Delphi method - Dong, Wenli; Zhu, Lixiong; Li, Wangming (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2017)
The current researches on the post-hoc evaluation on the implementation of historic city conservation planning in China confront dual complexity in their evaluation framework and criteria. Their evaluation methods are primarily based on experimentalism and qualitative descriptions, while the criteria lack subjective measurements, as well as the assessment of the feedbacks from citizens. Moreover, a feasible modelling method is needed for the establishment of a robust and feasible evaluation framework. It requires the utilization of a proper statistic method to refine the multi-criteria decision making (MCDM) method which are mostly adopted in urban planning implementation assessment. This paper aims to develop a methodology framework for the assessment of historic city conservation planning implementation in China, which can deal with the complexity and feasibility of the post-hoc evaluation. The initiative evaluation framework and a set of standards are primarily established. The framework is built based on